2013
DOI: 10.1002/mrc.4007
|View full text |Cite
|
Sign up to set email alerts
|

Four‐bond deuterium isotope effects on the chemical shifts of amide nitrogens in proteins

Abstract: An approach towards precision NMR measurements of four-bond deuterium isotope effects on the chemical shifts of backbone amide nitrogen nuclei in proteins is described. Three types of four-bond (15) N deuterium isotope effects are distinguished depending on the site of proton-to-deuterium substitution: (4)ΔN(N(i-1)D), (4)ΔN(N(i+1)D) and (4)ΔN(Cβ,(i-1)D). All the three types of isotope shifts are quantified in the (partially) deuterated protein ubiquitin. The (4)ΔN(N(i+1)D) and (4)ΔN(C(β,i-1)D) effects are by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Strangely enough, Ile and Val had the opposite sign to the other residues. In relation to this, a more specific study of the effect of deuteriation at the C-β carbon has been conducted by Tugarinov [12]. Recently, Smith et al [13] found similar values for perdeuteriated proteins in a solid state study of HET fibrils, but they did not study these further for reasons of variying pH.…”
Section: Nmrmentioning
confidence: 99%
“…Strangely enough, Ile and Val had the opposite sign to the other residues. In relation to this, a more specific study of the effect of deuteriation at the C-β carbon has been conducted by Tugarinov [12]. Recently, Smith et al [13] found similar values for perdeuteriated proteins in a solid state study of HET fibrils, but they did not study these further for reasons of variying pH.…”
Section: Nmrmentioning
confidence: 99%